Adaptive Cartesian and torsional restraints for interactive model rebuilding. Issue 4 (7th April 2021) - Croll, Tristan Ian; Read, Randy J.
Abstract : New forms of adaptive or top‐out distance and torsion restraints are described that are suitable for restraining a model to match a reference structure during interactive rebuilding. In addition, their implementation in ISOLDE is described, along with some illustrative example applications. Abstract : When building atomic models into weak and/or low‐resolution density, a common strategy is to restrain their conformation to that of a higher resolution model of the same or similar sequence. When doing so, it is important to avoid over‐restraining to the reference model in the face of disagreement with the experimental data. The most common strategy for this is the use of `top‐out' potentials. These act like simple harmonic restraints within a defined range, but gradually weaken when the deviation between the model and reference grows beyond that range. In each current implementation the rate at which the potential flattens at large deviations follows a fixed form, although the form chosen varies among implementations. A restraint potential with a tuneable rate of flattening would provide greater flexibility to encode the confidence in any given restraint. Here, two new such potentials are described: a Cartesian distance restraint derived from a recent generalization of common loss functions and a periodic torsion restraint based on a renormalization of the von Mises distribution. Further, their implementation as user‐adjustable/switchable restraints in ISOLDE is described and their use in some real‐world examples is demonstrated.